2015
DOI: 10.1111/jnc.13274
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in NPY‐positive neurons and dysregulation of excitability in young senescence‐accelerated mouse prone 8 (SAMP8) hippocampus precede the onset of cognitive impairment

Abstract: The senescence-accelerated mouse prone 8 (SAMP8) strain is considered a neurodegeneration model showing agerelated cognitive deficits with little physical impairment. Young SAMP8 mice, however, exhibit signs of disturbances in development such as marked hyperactivity and reduced anxiety well before the onset of cognitive impairment. As the key enzyme in local regulation of thyroid hormone (TH) signaling, type 2 deiodinase, was significantly reduced in the SAMP8 hippocampus relative to that of the normally agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…In the dentate gyrus, this could contribute to neuronal hyperexcitability reducing the threshold for the development of temporal lobe seizures that often occur in JNCL patients ( Zhang and Buckmaster, 2009 ). Selective loss of NPY + interneurons seems to precede cognitive impairment in a mouse models of accelerated senescence ( Sawano et al, 2015 ) and might therefore be particularly detrimental in disease progression also in the Cln3 Δex1-6 mouse model and JNCL patients. Recently, it has been shown that NPY itself is important for neuroprotection and modulation of synaptic plasticity, memory, anxiety-related behavior, and stress resilience ( Gøtzsche and Woldbye, 2016 ; Reichmann and Holzer, 2016 ), all of which are core features in JNCL.…”
Section: Discussionmentioning
confidence: 99%
“…In the dentate gyrus, this could contribute to neuronal hyperexcitability reducing the threshold for the development of temporal lobe seizures that often occur in JNCL patients ( Zhang and Buckmaster, 2009 ). Selective loss of NPY + interneurons seems to precede cognitive impairment in a mouse models of accelerated senescence ( Sawano et al, 2015 ) and might therefore be particularly detrimental in disease progression also in the Cln3 Δex1-6 mouse model and JNCL patients. Recently, it has been shown that NPY itself is important for neuroprotection and modulation of synaptic plasticity, memory, anxiety-related behavior, and stress resilience ( Gøtzsche and Woldbye, 2016 ; Reichmann and Holzer, 2016 ), all of which are core features in JNCL.…”
Section: Discussionmentioning
confidence: 99%
“…Senescence‐accelerated mice display loss of a neuropeptide Y‐positive subpopulation of hippocampal GABAergic neurons, which precedes cognitive impairment, and may be linked to longer lasting epileptiform activity (Sawano et al . ). Other work similarly concludes that the hippocampal neuropeptide Y system and its Y(2) receptors are associated with memory failure although here the model is one of methamphetamine intoxication (Goncalves et al .…”
Section: Peptidergic Transmission Signalling and Pathobiologymentioning
confidence: 97%
“…Neuropeptide Y continues to attract attention and when administered intracerebroventricularly was protective against hippocampal damage, stimulated endogenous neurogenesis and was considered to have potential for the management of temporal lobe epilepsy (Corvino et al 2012). Senescenceaccelerated mice display loss of a neuropeptide Y-positive subpopulation of hippocampal GABAergic neurons, which precedes cognitive impairment, and may be linked to longer lasting epileptiform activity (Sawano et al 2015). Other work similarly concludes that the hippocampal neuropeptide Y system and its Y(2) receptors are associated with memory failure although here the model is one of methamphetamine intoxication (Goncalves et al 2012).…”
Section: Peptidergic Transmission Signalling and Pathobiologymentioning
confidence: 99%
“…However, the alteration of GABAergic interneurons in the hippocampus has not been clearly identified in CCH so far, even though other pathological changes including neuronal damage, glial activation and oxidative stress have been already reported [6,10,16]. Parvalbumin (PV, a calcium-binding protein)-, neuropeptide Y (NPY, a neuropeptide)-and somatostatin (SOM, another neuropeptide)-positive cells are three well-known subclasses of GABAergic interneurons [17,18] and tend to have an essential role in the modulation of cognitive ability [19][20][21][22]. PV-positive interneurons in CA1 of hippocampus are required for spatial working [19].…”
Section: Introductionmentioning
confidence: 99%
“…NPY and its receptors also take a part in the modulation of neuronal functions such as learning and memory [20], and NPY-pretreatment was found to be beneficial in preventing impairments in spatial memory in AD models [25]. SOM in the brain inhibits the excitatory synaptic transmission, and plays a crucial role in memory and cognition [17,21].…”
mentioning
confidence: 99%